27x-19-39x=-65

Simple and best practice solution for 27x-19-39x=-65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27x-19-39x=-65 equation:


Simplifying
27x + -19 + -39x = -65

Reorder the terms:
-19 + 27x + -39x = -65

Combine like terms: 27x + -39x = -12x
-19 + -12x = -65

Solving
-19 + -12x = -65

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + -12x = -65 + 19

Combine like terms: -19 + 19 = 0
0 + -12x = -65 + 19
-12x = -65 + 19

Combine like terms: -65 + 19 = -46
-12x = -46

Divide each side by '-12'.
x = 3.833333333

Simplifying
x = 3.833333333

See similar equations:

| -3(2x+3)=6x+9 | | -0.1x+1.25=-0.5x+4.45 | | 8-9t=21r-17 | | (6+y)(2y+3)=0 | | 6p-16p=70 | | 3w+2-w=-3 | | 45x-21-17x=-63 | | 84=2k-5(2k-4) | | 3(x-1)+41=x-7(x+1) | | 6(4T+1)-13=T-(T+6) | | 6x+16=-2+8x | | 24x-81+7x=19 | | 25+10(12-x)=(2x-7) | | 84=-6(6+5x) | | 18^(1/3) | | 2.5/6=h/9 | | 8/12+9k/12=7/12 | | (2m+7)-(3-4m)=0 | | 2.5p-28=2p+26 | | y=5/4x+b | | 1.75m=21 | | 7v^2+35v-42=o | | 6(x+2)=8x+2-2x+10 | | 4.05p+0.9=4.50p | | -3x-5(x+6)=-33-7x | | 16w-18w=4 | | d-(4d-7)=5d-(d+21) | | -25/6+13/10 | | -3.2=I+(-0.2) | | 32/3=57/9 | | 35=-3x-15 | | 2x-9x+46=3x+36 |

Equations solver categories